Wpływ Wstępnego Plastycznego Rozciągania na Moduł Younga Mosiądzu i Niskowęglowej Stali - Litoński, J.; Klepaczko, J. (Engineering Transactions, 1964)
The paper presents the results of some tests on the change of Young's modulus of CuZn37 brass. The paper and 0,04%C carbon steel caused by plastic tensile strain. Young's modulus is understood as the slope of the initial part of the stress-strain diagram which has been found common for loading and unloading.It is found that the influence of plastic strain on the modulus is insignificant. Young's modulus of brass slightly increases when the initial plastic strain rises. After elongation to 19%, the highest change of the modulus is 4.4% of the value for annealed metal. It is believed that the increase of modulus is due to the preferred orientation of grains.For steel stretched to 4% and 7% no change of modulus is observed although it is possible that immediately after plastic deformation the modulus becomes somewhat lower and assumes its initial value after some hours. For, in that time (in the small stress region) loop type stress strain diagrams are observed, the slopes of the initial portion loading and unloading curve of which are 0.5-2.1% lower than the modulus of the annealed metal.During the tests, attention was paid to some rheological phenomena.